Pemidanaan Terhadap Pelaku Tindak Pidana Pengangkutan Elpiji Tanpa Izin Usaha Pengangkutan (Studi Putusan PN. Malang No. 720/Pid.Sus/2015/PN.Mlg. dan Putusan PN. Palangkaraya No. 335/Pid.Sus/2016/PN. Plk) - Alvi Syahrin; M Hamdan; Jusmadi Sikumbang; Jivo Sulistiawan (Jurnal Pencerah Bangsa, 2023)
Licensing procedures for transporting LPG according to the laws and regulations in Indonesia are technically not regulated in Law Number 22 Year 2001 concerning Oil and Gas and Government Regulation Number 36 of 2004 concerning Downstream Oil and Gas Business Activities which have been amended by Government Regulation Number 30 of 2009. The prosecution of business actors carrying out transportation of LPG without transportation business permits consists of principal penalties, namely imprisonment, imprisonment, criminal penalties as stipulated in Article 53 letter b of Act Number 22 of 2001 concerning Oil and Gas and also criminal additions consisting of revocation of rights or seizure of goods used for or obtained from criminal acts in Oil and Gas business activities included in Article 58 of Act Number 22 of 2001 concerning Oil and Gas